Preparation and Characterization of Modified Nylon 66 Membrane for Blood Purification - Shakaib, M.; Iqbal, Ahmed; R. M., Yunus; M. Z., Noor (Taylor & Francis, 2014)
Membranes were synthesized using polyamide (nylon 66) and monosodium glutamate (MSG) additive. The membranes with higher concentration of MSG additive were found to be thermally more stable and of porous structure. Due to porous structure, the permeation rate of impurities in blood through the membrane was increased. The effect of coagulant liquid temperature was also investigated and it was shown that increasing/decreasing the temperature does not significantly affect the performance of the polyamide-MSG membrane.